Epsilon-Near-Zero Absorber by Tamm Plasmon Polariton - Rashid G. Bikbaev; Stepan Ya. Vetrov; Ivan V. Timofeev (Photonics, 2019)
Two schemes of excitation of a Tamm plasmon polariton localized at the interface between a photonic crystal and a nanocomposite with near-zero effective permittivity have been investigated in the framework of the temporal coupled-mode theory. The parameters of the structure have been determined, which correspond to the critical coupling of the incident field with a Tamm plasmon polariton and, consequently, ensure the total absorption of the incident radiation by the structure. It has been established that the spectral width of the absorption line depends on the scheme of Tamm plasmon polariton excitation and the parameters of a nanocomposite film. The features of field localization at the Tamm plasmon polariton frequency for different excitation schemes have been examined. It has been demonstrated that such media can be used as narrowband absorbers based on Tamm plasmon polaritons localized at the interface between a photonic crystal and a nanocomposite with near-zero effective permittivity.